The PorX response regulator of the Porphyromonas gingivalis PorXY two-component system does not directly regulate the Type IX secretion genes but binds the PorL subunit. - Maxence S Vincent; Eric Durand; Eric CASCALES (Frontiers in Cellular and Infection Microbiology, 2016)
The Type IX secretion system (T9SS) is a versatile multi-protein complex restricted to bacteria of the Bacteriodetes phylum and responsible for the secretion of surface attachment of diverse proteins that participate to S-layer formation, gliding motility or pathogenesis. The T9SS is poorly characterized but a number of proteins involved in the assembly of the secretion apparatus in the oral pathogen Porphyromonas gingivalis have been identified based on genome substractive analyses. Among these proteins, PorY and PorX encode typical two-component system (TCS) sensor and CheY-like response regulator respectively. Although the porX and porY genes do not localize at the same genetic locus, it has been proposed that PorXY form a bona fide TCS. Deletion of the porX in P. gingivalis causes a slight decrease of the expression of a number of other T9SS genes, including sov, porT, porP, porK, porL, porM, porN and porY. Here, we show that PorX and the soluble cytoplasmic domain of PorY interact. Using electrophoretic mobility shift, DNA-protein co-purification and heterologous host expression assays, we showed that PorX does not bind and does not directly regulate expression of the T9SS genes. Finally, we show that PorX interacts with the cytoplasmic domain of PorL, a component of the T9SS membrane core complex and propose that the CheY-like PorX protein might be involved in the dynamics of the T9SS.